PERCEIVED BARRIERS TO LEISURE-TIME PHYSICAL ACTIVITY IN THE BRAZILIAN POPULATION - Rech,Cassiano Ricardo (2018)
ABSTRACT The aim of this study was to synthesize and analyze scientific evidence of the perceived barriers to leisure-time physical activity (PA) in the Brazilian population. The Lilacs, SciELO, PubMed, ScienceDirect and Web of Science journal databases were reviewed and the number of reports of each barrier to PA, grouped according to the level of determinants of the social ecological model (intrapersonal, interpersonal and environmental) was analyzed. We found 25 studies (11 in adolescents, 8 in adults and 6 in older adults), totaling 62,678 reports of barriers to PA. The studies were conducted in the South (n=15), Southeast (n=7), and Northeast (n=2) regions, and one study also included different regions of Brazil. Overall, about seven out of every 10 reports on barriers to PA involved intrapersonal barriers. Adults and older adults had a higher proportion of reports of intrapersonal barriers (84.8% and 74%, respectively), than adolescents (47.8%). There are still few studies with older adults, children, and in populations of the Midwest and North of the country. The most frequently reported barriers to PA among adolescents were lack of company, lack of social support from family and friends, unsuitable climate and limited access to spaces for PA. Lack of motivation and lack of time were the most frequently reported barriers in adults, whereas in older adults the predominant barriers were lack of motivation and diagnosed disease or physical limitation. PA promotion programs need to take into account the different barriers to PA, since these are specific to age groups. Level of Evidence II; Systematic Review of Level II Studies.